Autism in Peru: current status - Baquerizo-Sedano, Marilia (2023)
This review presents the current state of autism spectrum conditions (ASC) in Peru, including epidemiology, legal framework, education and health services. CEA are characterized by persistent difficulties in communication, social interaction, and restricted and repetitive behaviors and interests. The global prevalence of CEA is around 1%. In Peru, there are no reliable epidemiological studies on the prevalence of CEA. In 2014, the Law for the Protection of People with Autism Spectrum Disorder was approved, which allowed the development of a national plan for the period 2019-2021, which was partially fulfilled. In education, students with CEA were predominantly served in public institutions with guides and resources from the Ministry of Education. Regarding health services, in 2021, 12,325 people with CEA were cared for by the public sector, 78% between 1 and 11 years old. In conclusion, although certain progress has been made to benefit the population with CEA in Peru, there are still problems in access to diagnosis and specialized services.